The enactment of public participation in rulemaking: a comparative analysis [dataset] - De Francesco, Fabrizio; Tosun, Jale (Universität, 2024)
These are the data for the replication of the statistical analysis in the article "The Enactment of Public Participation in Rulemaking: A Comparative Analysis". The dataset contains time-series (1995-2015) cross-sectional (39 OECD countries) observations, in csv format which was created for the purpose of explaining the adoption of legislations allowing public participation in and judicial review of rulemaking. The corresponding codebook lists the used variables and sources. The replication codes are for Stata. (2022-11-04)
Gesehen am 16.09.2024
Keywords: Forschungsdaten; Datenbank